Peritoneal Dialysis Associated Peritonitis in Children With End-stage Renal Disease: A Single Center Experience in Iran: Peritoneal Dialysis Associated Peritonitis in Children - Shajari, Ahmad; Amiri Bakhtiari, Marzieh; Golshan Tafti, Mohammad (Journal of Pediatric Nephrology, 2023)
Background and Aim: The present study aimed to evaluate the frequency and risk factors of peritonitis end-stage renal disease (ESRD) pediatrics on peritoneal dialysis (PD) in Yazd City, Iran. Methods: This cross-sectional study was conducted on ESRD pediatrics on PD in Shahid Sadoughi hospital, Yazd City, Iran from 2016 to 2020. Demographic characteristics, such as age, sex, body mass index (BMI) at the commencement of PD, underlying medical conditions, the microbiology of peritonitis, and the recovery rate were investigated. Results were evaluated using SPSS software, version 26 (SPSS Institute, Inc., Chicago, IL, USA). Results: A total of 23 children (56.5% females) were included in this study. The Mean±SD age was 13.30±4.38 years, and the mean BMI was 15.71±5.53. PD-associated peritonitis was diagnosed in 18 cases (78.3%). A total of 21.7% had at least one underlying disease. No significant relationship was observed between sex (P=0.9), mean age (P=0.41), mean BMI (P=0.24), and underlying condition (P=0.29) according to pediatrics with and without PDassociated peritonitis. Bacterial and fungal infections were responsible for peritonitis in 15 (62.5%) and 3 (13%) pediatrics on PD, respectively. Conclusion: The frequency of PD-associated peritonitis in the ESRD children of our study was 78.3%.